Green Open Space Functions in Kauman Area, Semarang City, Indonesia - Intan Muning Harjanti; Pratamaningtyas Anggraini (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
Based on the results of identification and analysis related to the functions of green open space in Kelurahan Kauman, both private and public green open space, it was found that private green open space located in residential areas, office areas, education area, and in the worship area. Whereas existing public green open space is in the form of active parks, passive parks, green lane along the road border, green lane along the river border and green green space on the medians road. Private green open space in residential areas has ecological, economic and aesthetic functions; Private green open space in office areas is dominated by ecological functions; while green space in the areas of education, worship, trade and services, is dominated by ecological and aesthetic functions. Whereas public Green Open Space in the form of urban park has an economic function; Green Open Space green lane in the form of road borders, island road, and road median has ecological and aesthetic function; and Green Open Space with specific function in the form of river borders has the ecological and aesthetic function.